Le destin n'est pas inéluctable : évaluation des effets probables du libre-échange nord-américain sur la politique étrangère du Canada - Schmitz-Le Grand, Gerald (Études internationales, 1991)
This article with minor revisions, was originally presented as a paper at the annual meeting of the Canadian Political Science Association in Victoria, B.C., May 27, 1990. Since then, Canada has been accused of simply following Washington's lead in sending troops to the Gulfand in seeking to join United States-Mexico free trade negotiations. These developments do not alter the paper's challenging conclusion : namely, that the current bilateral free-trade regime neither obliges nor justifies a subordinate Canadian foreign policy — however much the terms of the Free Trade Agreement may impinge on the international dimensions of some Canadian policies (e.g., on energy and investment), and notwithstanding the potential momentum (but uncertain prospects) of North American integration. Free trade, in fact seems to have increased, not reduced, the salience of the national question in Canada. As well, the Gulf crisis is a test more of United Nations resolve than bilateral solidarity. And on the trade front, Canada has been reminded of the extent to which it remains on its own. U.S. negotiators were angered by Canada's middle-ground position on agricultural subsidies - the issue over which GATT talks collapsed, increasing Canadian vulnerability. Moreover, Canadian participation in U.S.Mexico trade negotiations has been privately less welcome than the official public rhetoric suggests. More than ever perhaps, Canadian national interests depend on strong international diplomacy mode no less necessary, if arguably encumbered, by the evolving context of continental free trade.